New Leadership Through New Lightness - Dow Chemical Company (1937)
Print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. The advertisement features a woman against a plain background holding a Hoover vacuum cleaner made with Dowmetal. The accompanying text describes Hoover as the first company to adopt Dowmetal for the production of a household appliance, the Hoover One Fifty model. The text attributes sales of the vacuum cleaner to the "amazing lightness" of Dowmetal. This advertisement appeared on page 157 of a 1937 edition of Fortune.
Keywords: Dow Chemical Company; Advertising; Household appliances; Chemical industry; Corporations; Magnesium; Magnesium alloys; Magnesium industry and trade; Women in advertising; Advertising, Industrial